The Role of Plant Cell Wall Proteins in Response to Salt Stress. (19th January 2014) - Zagorchev, Lyuben; Kamenova, Plamena; Odjakova, Mariela
Abstract : Contemporary agriculture is facing new challenges with the increasing population and demand for food on Earth and the decrease in crop productivity due to abiotic stresses such as water deficit, high salinity, and extreme fluctuations of temperatures. The knowledge of plant stress responses, though widely extended in recent years, is still unable to provide efficient strategies for improvement of agriculture. The focus of study has been shifted to the plant cell wall as a dynamic and crucial component of the plant cell that could immediately respond to changes in the environment. The investigation of plant cell wall proteins, especially in commercially important monocot crops revealed the high involvement of this compartment in plants stress responses, but there is still much more to be comprehended. The aim of this review is to summarize the available data on this issue and to point out the future areas of interest that should be studied in detail.